2020
DOI: 10.1016/j.foodchem.2020.126221
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of cereal monosaccharides, xylo- and arabinoxylo-oligosaccharides and uronic acids using HPAEC-PAD

Abstract: Xylo-and arabinoxylo-oligosaccharides (XOS and AXOS) are of interest for their prebiotic activity. The production of these oligomers might be accompanied with monosaccharides.The measurement of both oligosaccharides and monosaccharides usually requires two methods. The current work presents an HPAEC-PAD method based on gradient elution of aqueous solvents sodium hydroxide and sodium acetate, in contrast to conventional isocratic elution, for the simultaneous separation of 16 standards of monosaccharides, xyloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This is another technique used in OS characterization and it offers specific and sensitive detection, as well as good OS separation [135]. In a recent study, this technique has allowed the separation and the quantification of XOS and AXOS, with a DP up to 6, mixed together [136], however it has some limits, such as the progressive loss of detector signal during the analysis, the expensive replacement of disposable electrodes, and the difficulty in separating and characterizing branched OS [135]. In particular, in AXOS analysis, it has been observed that the position of substituent arabinose affects the retention time, and that some of these AXOS can elute simultaneously, which complicates their identification [137].…”
Section: Characterization Of Obtained (A)xosmentioning
confidence: 99%
“…This is another technique used in OS characterization and it offers specific and sensitive detection, as well as good OS separation [135]. In a recent study, this technique has allowed the separation and the quantification of XOS and AXOS, with a DP up to 6, mixed together [136], however it has some limits, such as the progressive loss of detector signal during the analysis, the expensive replacement of disposable electrodes, and the difficulty in separating and characterizing branched OS [135]. In particular, in AXOS analysis, it has been observed that the position of substituent arabinose affects the retention time, and that some of these AXOS can elute simultaneously, which complicates their identification [137].…”
Section: Characterization Of Obtained (A)xosmentioning
confidence: 99%
“…According to the method reported in a previous study (Alyassin et al, 2020), compositional monosaccharide analysis of PPPs was carried out with a Dionex ICS-3000 Ion Chromatography System (Dionex Corporation, Sunnyvale, CA, USA) containing an AS50 autosampler, an ICS-3000 dual pump, and an ICS-3000 DC.…”
Section: Hpaec-pad Analysismentioning
confidence: 99%
“…An application of HPAEC-PAD is the recent development of a method based on gradient elution of aqueous solvents sodium hydroxide and sodium acetate, in contrast to conventional isocratic elution. The method allowed the simultaneous separation of 16 standards of monosaccharides, xylo-oligosaccharides, arabinoxylo-oligosaccharides, and uronic acids from wheat bran using a CarboPac PA 200 column [125].…”
Section: Ion Exchange Chromatographymentioning
confidence: 99%